Workin' on the Contract: st Lucian Farmworkers in Ontario, A study of International Labour Migration - Larkin, Sherrie N. (My University, 1998)
This dissertation examines the seasonal round of st Lucian contract workers who travel to Ontario every year for temporary employment in the Foreign Agricultural Resources Management Service program (FARMS). The study's focus is divided among Ontario growers as employers, st Lucian agricultural workers as employees, residents of a rural town in Southwestern Ontario, and governmental departments that influence the FARMS program in Canada and in st Lucia. The main argument of the dissertation is that labour migration has been an integral part of st Lucian history since emancipation on the island. It is both an economic strategy and a symbol of the freedom emancipation promised. While factors external to the island, such as the need for agricultural labour in Ontario and a long history of connections between Canada and the British West Indies influence where st Lucians travel, the propensity of these men and women to leave the island and return can only be explained in terms of st Lucia's history as a British colony. Within this history, labour migration emerges in conjunction with other strategies of enduring yet resisting the plantation economy that characterized the island for centuries. Although "workin' on the contract" in Canada is used by st Lucians for individual social and economic goals, it derives its meaning from the shared cultural beliefs and values of the island's society.
Keywords: anthropology; farmworkers; labour migration; Agricultural and Resource Economics; Anthropology; International and Area Studies; Agricultural and Resource Economics